ANALISIS KETERAMPILAN SHORT PASS DAN LONG PASS SEPAKBOLA PADA SSB KAKI MAS MALANG - NURUL AZIZ; Luthfie Lufthansa; Rendis Eka Arisandi; Ferri Anggarusi Findrananta; Emilia Jefanggi Lolita Widiantini (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
In soccer, one of the basic skills that must be mastered by soccer athletes is short-pass and long-pass skills. This is because the short pass & long pass skills are good, fast, and directed, besides that athletes are also required to be able to coordinate both basic techniques with one another. So that both basic techniques with one can be implemented in harmony. The method used in this study was a survey method with 25 players as research subjects. From the analysis of the data on the short pass and long pass skills test results of SSB Kaki Mas Malang football players where on average the category is in the moderate category, while only 7 players are in the very good category. From the results above, it can be seen that from the aspect of the players who got test results in the moderate category, there were 18 players, while those who got test results in the Very Good category were 7 players. We can analyze that so far the training process that has been given to the players or athletes has been quite good. Based on the results of these tests, the coach can make a benchmark in further improving short-pass and long-pass soccer skills both individually and as a team. It can be seen that the coach is able to motivate the players to participate in training activities. The coach is competent in managing the team well so that training activities can be controlled and the coach can create a pleasant feel for the player's training activities so that the players are excited when participating in the training program. It has been proven that several players have actively contributed. Apart from that, the training atmosphere is fun, it can be proven that there are enthusiastic players during training, then serious when participating in activity until the players are responsible for the tasks set by the coach.